The Relationship Between Organizational Culture and Organizational Commitment - A Study of Employees in Perbadanan Kemajuan Negeri Kedah - Anita, Salleh (2012)
Since the year 1965 after its establishment, PKNK has undergone a transformation process which began with a small office building and comprises a total of eight employees to large organizations with over 140 employees with a vision to be an excellent knowledge of the organization in driving the development of state of Kedah Darul Aman. The amalgamation of a number of employees have bring together an array of people and perceptions , and therefore a myriad of organizational cultures are combined. The organizational culture of an organization has an effect on the organizational commitment of its employee’s. A fit between the organizational culture and the employees will increase the organizational commitment of those employees and contribute towards improved service delivery. The objective of this study are; to examine relationship between organizational culture and organizational commitment in which to examine relationship between communication and organizational commitment, to examine relationship between training and development and organizational commitment, to examine relationship between reward and recognition and organizational commitment and to examine relationship between teamwork and organizational commitment. A total of 100 questionnaires were distributed to 100 of staff at PKNK Kedah by hand and only 88 questionnaires were returned for analysis. Data were analyzed using both descriptive and inferential statistical analysis to interpret data.Research findings revealed there was a commitment existing among the respondents. Significant values for each element in independent variable which the items of communication, reward and recognition, training and development and teamwork were reliable which the reliability value for independent variables are Communication; 0.851, Training and Development: 0.703, Reward and Recognition: 0.581 and Teamwork; 0.694. It can be concluded that organizational culture has a significant effect on the organizational commitment of employees in PKNK and therefore can affect the service delivery within the public sector in Kedah.